Metaphors, temporalities and historical discourse of ‘aprismo tacneño’ in the nation (1931) - Vargas-Murillo, Alfonso Renato (2024)
This article analyzes the articulations between the regional historical memory of Tacna and the national discourse of Peruvian Aprismo deployed in the newspaper La Nación in 1931. It examines the strategies by which Tacna's Aprismo mobilized appeals to the local past to legitimize its candidates and project before public opinion in the elections to the Constituent Congress. Uses of references of the past, presentation of testimonies about previous patriotic participation of candidates and the instrumentalization of regional leaders in partisan rituals are identified. Likewise, debates around the opposition between the (anti)nationalism attributed to Aprismo and its own definition are studied in the post-electoral context.